Endowing biodegradable Zinc implants with dual-function of antibacterial ability and osteogenic activity by micro-addition of Mg and Ag (≤ 0.1 wt.%). (February 2023) - Chen, Kai; Ge, Wufei; Zhao, Li; Kong, Lingtong; Yang, Hongtao; Zhang, Xianzuo; Gu, Xuenan; Zhu, Chen; Fan, Yubo
Abstract: Infection remains the devastating complications associated with surgical fixation of bones fractured during trauma. In this study, we report a low-alloyed Zn-Mg-Ag that simultaneously has optimized strength degeneration profiles during degradation, outstanding antibacterial efficacy and osteogenic activity. Our results showed that Zn-0.05Mg-0.1Ag alloy had favorable mechanical properties (UTS: 247.8 ± 1.6 MPa, Elong.: 35 ± 2.2 %) and presented a better hold of mechanical integrity than pure Zn during 28 days corrosion, 2.6 % vs. 18.7 % reduction. After one-year of natural aging, the alloy still preserved an elongation of 24.07 ± 3.84 %. As verified by microbial cultures, Zn-0.05Mg-0.1Ag alloy demonstrated high antibacterial performance against Gram-positive and Gram-negative strains, as well as antibiotic-resistant strains ( MRSA ) in vitro and in vivo due to the synergistic antibacterial actions of Zn 2+ and Ag + . Meanwhile, Zn-Mg-Ag alloy also exhibited enhanced viability, osteogenic differentiation, and gene expressions of osteoblasts in vitro, as well as promoted osteogenic activity than pure Zn in the femoral condyle defect repair model. The co-releasing of Zn, Mg and Ag ions did not induce toxic side effects. Collectively, low alloyed Zn-0.05Mg-0.1Ag indicated long-lasting mechanical integrity during degradation, and presented the ability to synergistically inhibit bacteria and promote osteogenesis, possessing tremendous potential in treating implant-associated infections. Statement of significance: Infection after fracture fixation (IAFF) remains the most common and serious side effects of orthopedic surgery. Additionally, widespread antibiotic use contributes to the development of multi-drug resistant bacteria such as methicillin-resistant staphylococcus aureus ( MRSA ), which exacerbates IAFF treatment and prevention. IAFF treatment and prevention remain clinically challenging, so implants with dual antibacterial and osteogenic functions are in high demand. The antibacterial efficacy and osteogenic activity of low-alloyed Zn-Mg-Ag (≤0.1 wt.% Mg, Ag) alloys were investigated in vitro and in vivo . The results showed that micro addition of Mg and Ag could significantly improve osseointegration function, mechanical properties, and antibacterial performance. These quantification findings shed new light on the development and understanding of dual functional Zn-based orthopedic implants. Graphical abstract: Image, graphical abstract